Effects of visual spatial frequency on audiovisual interaction: an event-related potential study - Wu, Fengxia; Ren, Yanna; Hao, Tengfei; Yang, Jingjing; Wu, Qiong; Yang, Jiajia; Wang, Meng (Frontiers in Neuroscience, 2025)
Spatial frequency is a fundamental characteristic of visual signals that modulates the audiovisual integration behavior, but the neural mechanisms underlying spatial frequency are not well established. In the present study, the high temporal resolution of event-related potentials was used to investigate how visual spatial frequency modulates audiovisual integration. A visual orientation discrimination task was used, and the spatial frequency of visual stimuli was manipulated under three conditions. Results showed that the influence of visual spatial frequency on audiovisual integration is a dynamic process. The earliest audiovisual integration occurred over the left temporal-occipital regions in the early sensory stage (60–90 ms) for high spatial frequency conditions but was absent for low and middle spatial frequency conditions. In addition, audiovisual integration over fronto-central regions was delayed as spatial frequency increased (from 230–260 ms to 260–320 ms). The integration effect was also observed over parietal and occipital regions at 350–380 ms, and its strength gradually decreased at higher spatial frequencies. These discrepancies in the temporal and spatial distributions of audiovisual integration imply that the role of spatial frequency varies between early sensory and late cognitive stages. The findings of this study offer the first neural demonstration that spatial frequency modulates audiovisual integration, thus providing a basis for studying complex multisensory integration, especially in semantic and emotional domains.